Entrepreneurship and Small Firms - Deakins, David (London McGraw-Hill, 1999)
"Entrepreneurship and Small Firms, Second Edition combines an incisive analysis of topical theories of entrepreneurship with practical examples, real-life case studies, and strategic business plans. Students of entrepreneurship will acquire a thorough understanding of the small business sector and the skills needed to analyse and evaluate business enterprises."--BOOK JACKET